2011
DOI: 10.1111/j.1467-8489.2011.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Off-farm employment and reasons for entering farming as determinants of production enterprise selection in US agriculture

Abstract: In today's agriculture, farmers consider off-farm employment and lifestyle goals in complex ways to select production enterprises. Data from USDA's Agricultural Resource Management Survey were used to examine how off-farm employment and 'reasons for entering farming' influence production enterprise selection in US agriculture. A two-stage analysis with a multivariate tobit model was used to examine the impact of off-farm employment as influenced by government farm programme payments, reasons for entering farmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…The study opted for the two limits multivariate Tobit model in contrast to individual domain Tobit model because it allows for the unobservables that determine women empowerment in one domain have a likelihood of being correlated to those of other domains. Very few studies have used this methodology in agriculture (Gillespie and Mishra, 2011;Ali et al, 2012) and is mostly used in economics in demand estimation (Ma et al, 2006 …”
Section: Modeling the Determinants Of Women Empowerment Domainsmentioning
confidence: 99%
“…The study opted for the two limits multivariate Tobit model in contrast to individual domain Tobit model because it allows for the unobservables that determine women empowerment in one domain have a likelihood of being correlated to those of other domains. Very few studies have used this methodology in agriculture (Gillespie and Mishra, 2011;Ali et al, 2012) and is mostly used in economics in demand estimation (Ma et al, 2006 …”
Section: Modeling the Determinants Of Women Empowerment Domainsmentioning
confidence: 99%
“…Livestock farmers, for example, are more likely to invest in buildings and less likely to invest in irrigation than other farmers. Past research has shown that livestock farming may suffer from the impermanence syndrome to a greater degree than other types of farming (Lopez et al, 1988;Lynch and Carpenter, 2003), and also that hobby farmers are attracted to this sector (Boyd, 1998;Gillespie and Mishra, 2011;McBride and Mathews, 2011). Irrigation necessarily implies field or high value crops, as well as an operation large enough to make this kind of investment worthwhile (Skaggs and Samani, 2005).…”
Section: Description Of Regression Analysis and Variablesmentioning
confidence: 99%
“…Gillespie and Mishra (2011) showed that, unlike crop and broiler producers, cattle producers were more likely to answer that they had entered farming to "invest in real estate" or for "outdoor activity" than to "develop a business to generate additional income." While Basarir and Gillespie's (2006) "maintain and conserve land" and Gillespie and Mishra's (2011) "invest in real estate" are not necessarily inconsistent with the goal of maximizing profit, differences in goal structure are evident. These differences in goal structure are likely due to relatively limited economies of size associated with this enterprise.…”
Section: Introductionmentioning
confidence: 97%
“…As such, cow-calf farms vary widely in economic and financial viability. While studies have examined cow-calf producer technology adoption patterns (Ward et al, 2008;Kim et al, 2008), economic efficiency (Featherstone et al, 1997;Samarajeewa et al, 2012), goal structure (Basarir and Gillespie, 2006;Gillespie and Mishra, 2011), and factors affecting profitability (Miller et al, 2001;Ramsey et al, 2005) mostly via regional analyses, few studies (McBride and Mathews, 2011) have focussed on the drivers of economic and financial viability of US cow-calf production on a national basis. Cow-calf farms have historically realized returns that have often either barely or not covered costs (Basarir and Gillespie, 2006), complicated further by systematic increases and decreases in cattle prices over time as illustrated by the roughly ten-year cattle cycle (Tomek and Robinson, 1981, p. 179).…”
Section: Introductionmentioning
confidence: 99%